2011
DOI: 10.1149/1.3631502
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Toward the Reduction of Performance-Limiting Defects in SiC Epitaxial Substrates

Abstract: Reduction of the performance-limiting defects in SiC epitaxial substrates is indispensable to further penetration of SiC devices into the power device markets. This paper provides an opportunity to overview the current issues in SiC epitaxial substrates, focusing on dislocation-related problems. Structural defects such as threading screw dislocations (TSDs) and basal plane dislocations (BPDs) as well as surface morphological defects on the epitaxial layers due to dislocations are of current concern. The paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The depth of these pits is typically 3-20 nm, and the pits are deeper for TSDs than for TEDs. 160) When the pits are created, local electric field crowding occurs, simply because of a geometric effect. 161) Fujiwara et al found that the negative effects of TSDs on the diode characteristics could be eliminated almost entirely by suppressing the formation of dislocation-induced pits.…”
Section: In-grown Stacking Faults and Other Defects In Epitaxial Layersmentioning
confidence: 99%
“…The depth of these pits is typically 3-20 nm, and the pits are deeper for TSDs than for TEDs. 160) When the pits are created, local electric field crowding occurs, simply because of a geometric effect. 161) Fujiwara et al found that the negative effects of TSDs on the diode characteristics could be eliminated almost entirely by suppressing the formation of dislocation-induced pits.…”
Section: In-grown Stacking Faults and Other Defects In Epitaxial Layersmentioning
confidence: 99%
“…2.3, where the defect engineering is closely linked to the control of carrier lifetimes. Regarding extended defects in SiC epitaxial wafers, several types of dislocations, 176) stacking faults, 177,178) and more macroscopic defects such as polytype inclusions 179) and stacking fault complex (formerly "carrot" or "comet" defects) 180) are present though micropipe defects have been almost eliminated (density: < 0.1 cm −2 ).…”
Section: Research On Sic Bipolar Devicesmentioning
confidence: 99%
“…Both TSDs and TEDs may extend from the substrate to the wafer surface and bring about small pit-like surface features [ 15 ], as shown in Fig. 3 b [ 25 ]. Typically, density of TEDs is about 8000–10,000 1/cm 2 , which is almost 10 times larger than that of TSDs.…”
Section: Defects In Sicmentioning
confidence: 99%